The sixes : a novel - White, Kate, 1950- (Harper, 2011)
"From the New York Times bestselling author of Hush and Cosmopolitan's editor-in-chief comes a new standalone thriller set in a college-town where a campus death sends one woman on a quest for truth and into the clutches of a deadly secret society"--